AN EXAMINATION OF THE RISKS OF HAZARDOUS TREES IN THE CONTEXT OF VANDALISM PREVENTION IN URBAN AREAS - Hamzah, Helmi; Dwiyanti, Fifi Gus; Hasan, Ramly; Abu Bakar, Karwina (PLANNING MALAYSIA, 2024)
It is essential to protect trees in urban areas, particularly those with defects and pose a hazard, to maintaining the longevity of the green infrastructure and the safety of the neighbourhoods. Defective trees (DTs) and hazardous trees (HTs) are often vandalised. Therefore, it is essential to understand the correlation between the vandalism index (VI) and hazard score (HS) of trees to implement strategies that effectively decrease risks and sustain the long-term health of urban green spaces. This present study aims to quantify the correlation between the HS and VI of trees, identify the unique effects of each element on the urban environment, and develop well-informed mitigation strategies. It also assesses the HSs of trees and quantifies their VIs to provide a comprehensive understanding of the risks associated with both factors in urban landscapes. The results of this present study indicate a positive correlation between the VI and HS of trees and identified tree size as an important element impacting their VI. Time constraints and accessibility, particularly when surveying broad areas, are some of the limitations of this present study as it used conventional methods of tree assessments. Nevertheless, tree managers can utilise its findings to make better management decisions as well as increase user comfort and security in urban settings. Furthermore, implementing these findings will enhance and beautify public areas as well as increase public safety.